One-pot Synthesis of Functionalized Benzimidazole-quinazolinone Derivatives - Beker, Huseyin Kerim; Kaban, Seniz (BENTHAM SCIENCE PUBL LTD, 2026)
Introduction/Objective Quinazolinone and aldehyde derivatives have emerged as important molecules in recent studies because of their wide spectrum of pharmacological and biological effects. They have recently attracted attention in synthesis and research. Combinatorial synthesis for this type of heterocycle has emerged in the literature over the last decade. In one-pot processes, atypical intermediates often play key roles in the overall transformation. An unusual coupling sequence occurs through nucleophilic addition to an in situ-formed Michael intermediate. This is followed by an electrocyclic cyclization step. Motivated by these findings, we focused on designing a convenient synthetic method for the preparation of benzimidazole-quinazolinone and heteroaryl aldehyde derivatives. This study aimed to create efficient MCR pathways using common starting materials to build benzimidazole and quinazolinone scaffolds. Methods In this study, we performed a one-pot, three-component reaction. We reacted 2-aminobenzimidazole, various substituted heteroaryl aldehydes, and dimedone in absolute ethanol. Analytical and spectroscopic data (NMR, GC-MS, IR, and UV) were used to characterize and verify the structures of the synthesized complexes. Results The lead was compound 4a (88% yield). This route enables efficient heterocycle assembly. GC-MS analysis confirmed that compounds 4e and 4f share the same base peak (m/z 266), suggesting a common fragmentation pathway due to structural similarities.Discussion An efficient one-pot method for the synthesis of benzimidazole[2,1-b]quinazolinone derivatives was developed, avoiding multi-step procedures, and spectroscopic analyses confirmed the successful formation of the target compounds, demonstrating the practicality of the method. Conclusion The compounds obtained represent promising starting points for structural modification, which could lead to the development of more active quinazoline-based derivatives.
Keywords: One-pot multi-component synthesis; 2-aminobenzimidazole; heteroaryl aldehyde; quinazolinones; GREEN; Chemistry